PELATIHAN PENGAJAR DAN PENGEMBANGAN PSIKOMOTORIK ANAK-ANAK MIGRAN DI SB AT-TANZIL HICOM KUALA LUMPUR MALAYSIA - Nurhayati, Nurhayati; Astono, Ari Dwi; Yustinah, Yustinah; Syarif, Tiara Almas (Jurnal Abdimas Bina Bangsa, 2024)
The continuity of the Cooperative business will not escape the problems that can be experienced in the future. If the Cooperative's problems are not immediately anticipated and resolved properly, it will be fatal to its sustainability. Therefore, strategic management and operational strategies in cooperative activities are very important to pay attention to. The purpose of the Community Service (PKM) activities at the Banyumanik Banyumanik Dairy Cooperative business in Semarang City is to provide strategic management assistance and operational strategies. This PKM uses the Participatory Action Research (PAR) method through strategic management and operations strategy assistance activities. The evaluation results of this PKM obtained the conclusion that knowledge of strategic management and operations strategy increased 80%, the ability of strategic management and operations strategy increased 75%, the ability to develop strategic management and operations strategy increased 84%, the skills to achieve competitive advantage through strategic management and operations strategy increased 90%, and the skills to develop and implement strategic management and operations strategy increased 90%.